Dietary intake and factors associated with malnutrition among chronic kidney disease patients: insights from a hospital based cross-sectional study - Hajira, Bibi; Akhtar, Sultan Zaffar; Adeeb, Humera; Haq, Ijazul; Afridi, Muhammad Samiullah (International Journal of Pathology, 2026)
Background: Chronic kidney disease (CKD) is a global health concern in both developed and developing countries. However, there is limited evidence on dietary intake and factors associated with malnutrition among CKD patients in our context. Therefore, this study determined dietary intake and predictors of malnutrition in CKD patients. Methods: In a cross-sectional study in adult CKD patients’ (n = 189; aged: 44.8 ± 10.09 years; stage 1-5) data on demographic factors, medical history and dietary intake was collected using multiple pass method. Anthropometric measurements including Mid upper arm circumference (MUAC), Body mass index (BMI), and Waist to Hip ratio (WHR) were used to assess nutritional status using CKD-specific cut-offs. Results: Malnutrition was present in 83.4% of patients. The average intake of energy and essential macronutrients and micronutrients were significantly (p < 0.05) lower than recommended intake. Factors significantly associated with malnutrition included gender (p = 0.01), low dietary intake of fibre (p = 0.03), calcium (p = 0.03), iron (p = 0.04) and zinc (p = 0.03). Furthermore, presence of oedema (p = 0.05), high serum creatinine (p = 0.03), low serum albumin (p = 0.02), presence of kidney stones (p = 0.05) and co-morbidities (p = 0.05) show significant association with malnutrition. Conclusion: The study highlights high burden of malnutrition among CKD patients, with dietary intake falling far below the recommended levels. There is a need for individualized dietary interventions, particularly in advanced CKD stages, to improve nutritional status and patient outcomes.